Transforming higher education through active engagement and creative teaching: Reflections and practices - Wojciechowska, M.; Gomes, S. (Novos Exemplos de práticas pedagógicas e estratégias de inovação pedagógica no Iscte, 2025)
This chapter explores a transformative approach to higher education that shifts from traditional, lecture‑based instruction to active, student‑centered learning grounded in creativity, empathy, and experiential engagement. Drawing on the context of the Bologna Process and inspired by Paulo Freire’s critical pedagogy, the authors reflect on their experience teaching Design Thinking and Public Presentations with Acting Techniques at Iscte. Through these courses, students engage in real‑world problem‑solving, improvisation, prototyping, and self‑expression – developing essential transversal skills such as communication, teamwork, empathy, and critical thinking. The chapter emphasizes the role of the educator as a coach and facilitator who creates emotionally intelligent learning environments where students are encoura‑ ged to take risks, collaborate, and co‑construct knowledge. Feedback is posi‑ tioned as a strategic, developmental tool that fosters growth, reflection, and motivation. Student feedback highlights increased confidence, autonomy, and personal transformation, while also pointing to areas for improvement, such as activity pacing and integration of real‑world challenges. The authors argue that for higher education to remain relevant in an unpredictable world, institutions must prioritize curricular flexibility, active methodologies, and a culture of innovation that supports both students and educators. Ultimately, the chapter calls for a redefinition of teaching as a relational, reflective, and human‑centered practice that empowers learners to thrive personally and professionally.